2020
DOI: 10.21873/invivo.12019
|View full text |Cite
|
Sign up to set email alerts
|

Azygos Vein Aneurysm Mimicking a Mediastinal Mass

Abstract: Background/Aim: Azygos vein aneurysm (AVA) is a rare thoracic pathological entity that mimics a posterior mediastinal mass as well as a right paratracheal mass. Usually asymptomatic, AVA is often accidentally discovered during routine chest x-rays; however, depending on the aneurysm size and complications, some symptoms may be present. The aim of this paper is to report a case of idiopathic AVA and to discuss its aetiology, embryonic origin, symptoms, complications, diagnostic methods and treatments. Case Repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Some authors consider that the most common primary pleural tumors are solitary pleural fibromas; however, leiomyoma must be included as an option during the differential diagnosis, even though it is a rare pathology (35). In fact, during the differential diagnosis other types of tumors should also be taken into consideration, such as neuromas, secondary lesions or other intrapleural tumoral masses (36,37). In our case, we chose a cautious intraoperative approach using a wide resection with oncological margins, as if we were removing a solitary pleural fibroma.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors consider that the most common primary pleural tumors are solitary pleural fibromas; however, leiomyoma must be included as an option during the differential diagnosis, even though it is a rare pathology (35). In fact, during the differential diagnosis other types of tumors should also be taken into consideration, such as neuromas, secondary lesions or other intrapleural tumoral masses (36,37). In our case, we chose a cautious intraoperative approach using a wide resection with oncological margins, as if we were removing a solitary pleural fibroma.…”
Section: Discussionmentioning
confidence: 99%
“…Dasika et al [ 13 ] and De Palma et al [ 14 ] reported cases of leiomyosarcoma of the azygos vein and epithelioid hemangio-endothelioma, respectively, and they advocated aggressive surgical therapy. Savu et al [ 15 ] reported that in cases of azygos venous aneurysm with complete thrombosis, surgery was recommended and must be performed with extreme care in order to prevent intraoperative embolism. Our patient had symptoms of back pain, chest tightness, and choking.…”
Section: Discussionmentioning
confidence: 99%
“…The routine paraclinical imaging examination for diagnosis and for the evaluation of extension is the CT examination ( Fig. 2 ) ( 22 , 27 , 32 ). Thus, a CT examination can show specific signs of parietal thoracic necrotizing fasciitis: signs of parietal collections, edema in the subcutaneous and fatty tissue, gas collections locally or with locoregional extension.…”
Section: Discussionmentioning
confidence: 99%